A pollen fatty acid enhances learning and survival in bumblebees. (18th August 2018) - Muth, Felicity; Breslow, Phillip R; Masek, Pavel; Leonard, Anne S
Abstract : Eating pollen may make bees better at learning about flowers. Although flowers offer both nectar and pollen, we know little about how bees learn in relation to both resources. We discovered that the 2 rewards interact to affect color learning: bees that ingested nectar containing a pollen fatty acid were better at learning. This effect may have been driven by bees "feeling better" after having consumed the fatty acid solution and thus being more driven to learn cues relating to it. Abstract: Learning associations between food-related stimuli and nutrients allows foragers to collect resources efficiently. In turn, the nutrients that foragers consume can themselves affect learning performance, through innate preferences for pre-ingestive stimuli, as well as post-ingestive reinforcement. Bees are insect models of learning and memory, yet the vast majority of this research concerns nectar (carbohydrate) rather than pollen (protein/lipid) rewards, despite the fact that many bees collect both simultaneously. We asked how one component of pollen surface chemistry, a free fatty acid (oleic acid), affected bees' performance in a nectar-learning task. We found that ingestion of oleic acid enhanced visual learning, likely through positive post-ingestive reinforcement. This was supported by our finding that although bees did not prefer to consume the oleic acid solution, its ingestion both decreased motor activity and increased survival. These results are a step towards understanding how nutritionally complex floral rewards may affect cognitive processes that underlie pollination mutualisms.